Energy and exergy analysis of a new flat-plate solar air heater having different obstacles on absorber plates - Akpinar, Ebru Kayak; Kocyigit, Fatih (Elsevier Sci Ltd, 2010)
This study experimentally investigates performance analysis of a new flat-plate solar air heater (SAH) with several obstacles (Type I, Type 11, Type 111) and without obstacles (Type IV). Experiments were performed for two air mass flow rates of 0.0074 and 0.0052 kg/s. The first and second laws of efficiencies were determined for SAHs and comparisons were made among them. The values of first law efficiency varied between 20% and 82%. The values of second law efficiency changed from 8.32% to 44.00%. The highest efficiency were determined for the SAH with Type II absorbent plate in flow channel duct for all operating conditions, whereas the lowest values were obtained for the SAH without obstacles (Type IV). The results showed that the efficiency of the solar air collectors depends significantly on the solar radiation, surface geometry of the collectors and extension of the air flow line. The largest irreversibility was occurring at the SAH without obstacles (Type IV) collector in which collector efficiency is smallest. At the end of this study, the energy and exergy relationships are delivered for different SAHs. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Energy analysis; Exergy analysis; Exergy efficiency; Solar air heater; Obstacles; Thermal efficiency